STATISTICAL LEARNING DIFFICULTIES ANALYSIS IN THE ERA OF PANDEMIC COVID-19 IN GUIDANCE AND COUNSELING COLLEGE STUDENTS - Meilla Dwi Nurmala; Stevany Afrizal; Meitami Sofiyanti (Universitas Sultan Ageng Tirtayasa, 2022)
Abstract: COVID-19 is a virus that spreads around the world. Indonesia is one of the affected countries. Everyone has only experienced the current conditions and situations, so that good adaptations and adjustments are needed in all aspects, including learning. Teachers implement online learning methods to students to minimize the risk of spreading the COVID-19. This research was done with a quantitative description method. The results showed that students' learning difficulties when learning at home online were inadequate facilities and internet networks, insufficient understanding of certain subjects, a learning atmosphere at home that was less conducive to the analysis of students' learning difficulties carrying out learning online COVID-19 pandemic period. This study aims to obtain information about the problems experienced by students in carrying out online statistics learning during the COVID-19 pandemic